PROTOTIPE RAIS-MR3 SEBAGAI INOVASI TATA KELOLA PEMERINTAHAN DESA PADA PROGRAM 200 ITIK RUMAH TANGGA SIPODECENG - Taufik Suherman; Rohady Ramadhan; Muhammad Rais Rahmat Razak; Rasdiana Mustapa (LPPM Universitas Abdurrab, 2026)
This study develops the Rais-MR3 Prototype as an innovative model of village governance that integrates four core pillars: Management, Regulation, Responsibility, and Result. The model aims to enhance transparency, accountability, and community participation in implementing the 200 Ducks per Household Program in Sipodeceng Village. Using a qualitative descriptive approach with a prototype development method, the research involved village officials, BUMDes managers, and beneficiary households as key informants. The findings reveal that while the program’s governance aligns socially with good governance principles, it remains largely conventional and lacks systematic digital integration. The Rais-MR3 implementation successfully strengthens actor coordination, standardizes regulations and SOPs, and establishes real-time, data-based public accountability. The study contributes an integrative model of digital village governance replicable for other local economic empowerment initiatives. Practically, it promotes digital literacy among village officials and aligns local systems with regional e-Government policies to realize adaptive and sustainable village governance.